Critical analysis of pandemic impact on AEC organizations: The covid-19 case - King, Sze Soon; Rahimi, A. Rahman; Muhammad Ashraf, Fauzi; Ahmad Tarmizi, Haron (Emerald Group Holdings Ltd., 2022)
Purpose: This study aims to investigate the interrelationships between COVID-19 pandemic impact and architectural, engineering and construction (AEC) organizations. To achieve that aim, the objectives are to: identify the critical pandemic impact (CPI) of COVID-19 on AEC organizations; compare the CPI between the different organization characteristics; and analyze the interrelationships between the CPI. Design/methodology/approach: A systematic literature review of 519 articles and in-depth interviews with 40 AEC practitioners were carried out, yielding 12 COVID-19 impacts. Then, data on the 12 impact’s criticality were collected through a survey among AEC practitioners. In total, 127 valid responses were received and analyzed using mean ranking analysis, analysis of variance and Spearman’s correlation. The findings were also compared with pandemic impacts from prior works. Findings: Five CPI exist among the 12 impacts, namely, “reduced construction productivity,” “reduced foreign investment in the construction industry,” “reduced demand on construction-related works,” “disruption in the supply chain” and “reduced number of public projects.” “Reduced foreign investment in the construction industry” and “reduced demand on construction-related works” significantly impact small-medium enterprises than large enterprises. Also, “disruption in the supply chain” and “reduced construction productivity” are recurring impacts in all countries compared. Finally, moderate relationships exist between “reduced foreign investment in the construction industry” and “reduced demand on construction-related works” and “disruption in the supply chain” and “reduced construction productivity.” Originality/value: The findings can be used to prioritize available resources in developing short-term responses for COVID-19. Also, action plans can be developed to mitigate the CPI from recurring.